NOx emissions for oxy-mild combustion of pulverized coal in high temperature pre-heated oxygen. (August 2018) - Perrone, D.; Castiglione, T.; Morrone, P.; Barbarelli, S.; Amelio, M.
Abstract: Oxy-MILD (Moderate or Intensive Low Oxygen Dilution) combustion is an attractive technology for increasing combustion efficiency and reducing the nitric oxides with respect to the conventional combustion in traditional boilers or furnaces. This technology is a combination of MILD combustion, which exploits the initial preheating of combustion air up to 800÷1300 °C and the simultaneous recirculation of the hot flue gases, and of Oxy-Combustion, which uses pure oxygen (greater than 95% purity) as oxidant instead of air. The combination of both technologies is expected to bring synergetic effects: NOx reduction, CO2 capture possibility, fuel flexibility and uniformity of heat fluxes and species concentrations. This study focuses, in particular, on the analysis, by a CFD approach, of the NOx emissions for Oxy-MILD combustion of pulverized coal in a new concept of industrial boiler. The boiler, fueled with a high-volatile coal, is equipped with five burners and three outlets of the combustion products, localized on the top wall. Each burner is made-up of a central pulverized coal jet surrounded by six preheated oxygen jets. This configuration allows the achievement of the MILD combustion in pure oxygen. Results show that the goal of NOx reduction with this combustion approach is achieved. A value of about 296 mg/Nm 3 @6%O2 at the boiler exit is obtained under Oxy-MILD conditions, which is significantly lower than 600-800 mg/Nm 3 @6%O2 obtained in a traditional boiler.